(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
One of the widely used units in Uzbek language that needs classification and analysis is the borrowed pattern compounds. This concept includes several units that are semantically and syntactically the same, but there is a difference between them. In the following years, in addition to the lexical layer of the Uzbek language, a number of units affecting the grammatical construction have entered. The article describes in detail the loan-calqued grammatical compounds, their characteristics, current research and problematic aspects.